Gustatory and olfactory responses to stimulation of the human insula. Issue 3 (30th August 2017) - Mazzola, Laure; Royet, Jean‐Pierre; Catenoix, Hélène; Montavont, Alexandra; Isnard, Jean; Mauguière, François
Abstract : Objective: Despite numerous studies suggesting the role of insular cortex in the processing of gustatory and olfactory inputs, the exact location of olfactogustatory representation in the insula remains controversial. Here we provide a functional mapping of olfactory–gustatory responses to stimulation of the human insular cortex. Methods: We reviewed 651 electrical stimulations of the insula that were performed in 221 patients, using stereotactically implanted depth electrodes, during the presurgical evaluation of drug‐refractory epilepsy. Results: Gustatory sensations were evoked in 15 (2.7%) of the 550 stimulations that elicited a clinical response. They were exclusively obtained after stimulation of a relatively delimited zone of insula, located in its mid‐dorsal part (posterior short gyrus). Six olfactory sensations (1.1%) could be obtained during stimulations of an insular region that partially overlapped with the gustatory representation. Interpretation: Our study provides a functional mapping of gustatory representation in the insular posterior short gyrus and the first detailed description of olfactory sensations obtained by direct stimulation of mid‐dorsal insula. Our data also show a spatial overlap between gustatory, olfactory, and oral somatosensory representation in the mid‐dorsal insula, and suggest that this part of the insula may be an integrated oral sensory region that plays a key role in flavor perception. It also indicates that dysfunction in this region should be considered during the evaluation of gustatory and olfactory epileptic seizures. Ann Neurol 2017;82:360–370